TRENDS OF RAINFALL AND MAIZE PRODUCTIVITY IN MALAWI - Kimaro, T. A.; Sibande, H. (Tanzania Journal of Engineering and Technology, 2018)
Daily rainfall data between 1966 and 2005 across all Agricultural Development Areas (ADDs) in Malawi was investigated to determine changes in selected rainfall characteristics and their impact on Maize productivity. Rainfall indices analyzed included rainfall amounts (annual and seasonal), onset, cessation, dry spells and length of rainy season. Man Kendal ' s trend test was applied to the time series of these indices to detect any trends in the time series. Water Requirement Satisfaction Index (WRSI) for maize crop was used to study the spatial-temporal variation of maize productivity and thus its linkage to rainfall. Definition of onset and cessation adopted from the Department of Meteorological Service (DMS) Malawi was used in demarcating seasons to extract seasonal rainfall amount, length and other parameters. The results of the study indicate that with the exception of Karonga ADD located at the Northern tip of the country there were no significant trends in all variables related to crop productivity including onset, cessation, rainfall amount and dry spells. The spatial and temporal variability of maize production in Malawi was captured quite well by the WRSI. The relationship between long-term average WRSI and maize yield (tonnes/ha) for different stations in Malawi had a correlation coefficient of 0.82 while the relationship of countrywide average WRSI and maize yield had a correlation coefficient of 0.75. Areas with low long term average WRSI like Shire valley also showed low productivity while those with higher WRSI like Mzimba and Salima ADD had a good yield. On average Malawi has sufficient rainfall to sustain rain-fed maize crop as most of the time (67%) rain-fall is enough to give an average yield. It was also found out that Malawi experience droughts and hence food shortages when WRSI value is close to or below 60%.